Propriedades de armazenagem de hidrogênio de materiais à base de magnésio e ferro preparados por moagem de alta energia e técnicas de deformação plástica severa - Asselli, Alexandre Augusto Cesario (2013)
In the doctoral research, the hydrogen storage properties of magnesiumiron based materials prepared by high energy ball milling and techniques of severe plastic deformation were studied. The materials were processed by ball milling under inert atmosphere and reactive milling under hydrogen pressure. The techniques of high pressure torsion, cold forging and rolling were used to prepare the materials in air. Several compositions of Mg and Fe reactants were used to study the behavior of hydrogen absorption and desorption of Mg2FeH6 and MgH2 based materials. The results showed that high energy ball milling was effective to synthesize Mg2FeH6, nevertheless, long milling times (> 12 h) were required and the sample were easily contaminated when exposed to air. Between the techniques of severe plastic deformation, the best results in terms of hydrogen absorption kinetics and capacity were achieved by cold rolling. These results were similar to the milled samples ones, however, cold rolling was carried out in air and with a processing time shorter than 1 minute. The formation mechanism of Mg2FeH6 was studied by measurements of hydrogen absorption kinetics and microstructural characterization through the techniques of X-ray diffraction and scanning and transmission electron microscopy. These analyses allowed to determine that Mg2FeH6 was formed with a columnar morphology by a diffusional process during the hydrogen thermal absorption. The effects of the addition of expanded natural graphite were evaluated to the samples prepared by high energy ball milling and cold rolling. The data showed that the use of this additive resulted in faster kinetics of hydrogen absorption and desorption of the magnesium-iron based materials.